2021
DOI: 10.3389/fcvm.2021.780762
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Anticoagulatory Treatment After Transcatheter Aortic Valve Replacement: A Retrospective, Observational Study on 4,800 Patients

Abstract: Background: Transcatheter aortic valve replacement (TAVR) has developed to the therapy of choice for patients with symptomatic severe aortic stenosis who are unsuitable for surgical aortic valve replacement and elderly patients with intermediate or high operative risk. However, the optimal anticoagulant therapy post-TAVR still remains a matter of debate.Aims: This study sought to investigate current anticoagulant treatment patterns and clinical outcome in patients undergoing TAVR.Methods: In a retrospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The ACM outcome was reported in eight studies 13 15 , 19 , 20 , 22 . No statistically significant difference was found between the APT and OAC groups with respect to ACM [8.35% versus 10.4%; RR:0.67; 95% CI:0.45–1.01; P =0.05; I 2 =76%] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACM outcome was reported in eight studies 13 15 , 19 , 20 , 22 . No statistically significant difference was found between the APT and OAC groups with respect to ACM [8.35% versus 10.4%; RR:0.67; 95% CI:0.45–1.01; P =0.05; I 2 =76%] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hohmann et al . 22 studied ACM in similar treatment and control arms and reported that APT is superior. DeBacker et al .…”
Section: Discussionmentioning
confidence: 99%
“…VHD and AF are frequently coexisting and both of them lead to an increased risk of death. Generally, AF can cause a 5-fold increase risk of stroke [3] , while transcatheter aortic valve replacement(TAVR) increases stroke risk by 3.95-fold [4] . In patients suffering from aortic stenosis, 40.7% have AF and 6.8% experienced new-onset AF after TAVR [5] .…”
Section: Introductionmentioning
confidence: 99%